THE ROLE OF FINANCIAL TECHNOLOGY (FINTECH) IN MANAGING UMKM FINANCE IN NORTH BENGKULU DISTRICT - Zoraya, Intan; Kamaludin, Kamaludin; Santi, Fitri; Rahmayanti, Dewi; Afandy, Chairil (Multifinance, 2025)
This study examines the role of financial technology (fintech) in improving financial literacy among Micro, Small, and Medium Enterprises (MSMEs) in North Bengkulu Regency. Along with the development of technology and people's need for more efficient financial services, fintech has emerged as a solution to facilitate financial transactions. However, the community's low understanding of fintech can lead to financial risks, especially for MSME groups that tend to be consumptive. The research involved socialization and education on the use of fintech, with a focus on its positive impact and how to use it wisely. The methods used included surveys, presentations, and interactive discussions with participants. The results of the activity showed an increase in participants' knowledge of fintech and its potential utilization to improve financial transactions. This activity is expected to encourage local economic growth and increase public awareness of the importance of financial literacy in the digital era. Therefore, continuous education and support are needed to ensure that people can optimally utilize fintech.